Perbandingan Sekuritisasi Imigrasi Era Barack Obama dan Donald Trump sebagai Strategi Keamanan Nasional Amerika Serikat - Isnaya Syahranisa; Nur Isdah Idris (Lembaga Pengembangan Kinerja Dosen, 2024)
Immigration has become a central issue in U.S. national security policy, especially after the events of September 11, 2001. The discourse around immigration is increasing, especially in the context of national security policy, which leads to the securitization of immigration. This process constructs immigration as a security threat, which justifies a strict political and policy response. In former President Obama's perspective, U.S. immigration policy has been focused on national security since the beginning of his presidency. This emphasis is manifested through increased border surveillance and inclusive and humane immigration law enforcement through the Deferred Action for Childhood Arrivals (DACA) program. Instead, Donald Trump's administration adopted a more secure approach, focusing on border security and immigration restrictions, including a controversial border wall and travel ban. This shift reflects a broader shift in U.S. domestic politics and global perceptions. Understanding these differences provides insight into how immigration policy impacts U.S. national and public security.